Documentation of Indigenous Knowledge on Mushroom Cultivation - M P Sagar , O.P.Ahlawat and B. Vijay, (Indian Journal of Extension Education, 2014)
Mushroom cultivation in India is being practised for the last four decades. During this period, mushroom growers haveamended several scientifically proven mushroom cultivation practices suiting to their own needs. The collection anddocumentation of such locally adopted practices is very important from view point of their validation and furtherrefinement. Thus, the present study was conducted by involving 400 established mushroom growers, andresearch/extension personnel using mailed questionnaire and structured interview schedule. A total of 10 ITKs werecollected on different aspects of button, oyster and paddy straw mushrooms. Majority of the collected ITKs were onbutton mushroom, while only a few on oyster and paddy straw mushrooms. The ITKs viz., pasteurization of buttonmushroom compost without injecting steam, use of burnt rice husk as casing material for button mushroom, mushroomgrowing in mud houses and thatched / sarkanda sheds, cooling system of thatched shed/pakka house, spray of urea andEnglish wishkey (alcohol) on mushroom beds, bunker system and under stacking aeration system for button mushroomcompost preparation, flat floor method of oyster mushroom cultivation and traditional outdoor and indoor methods ofpaddy straw mushroom cultivation were collected. These ITKs need to be validated and refined through experiments,experts opinion and scientific literature.